2014
DOI: 10.4103/1673-5374.130103
|View full text |Cite
|
Sign up to set email alerts
|

Sensory reinnervation of muscle spindles after repair of tibial nerve defects using autogenous vein grafts

Abstract: Motor reinnervation after repair of tibial nerve defects using autologous vein grafts in rats has previously been reported, but sensory reinnervation after the same repair has not been fully investigated. In this study, partial sensory reinnervation of muscle spindles was observed after repair of 10-mm left tibial nerve defects using autologous vein grafts with end-to-end anastomosis in rats, and functional recovery was confirmed by electrophysiological studies. There were no significant differences in the num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…These measurements are consistent with the 42.29 ± 3.04 µm maximal diameter of muscle spindles in the gastrocnemius muscles of adult Lewis rats (Elsohemy et al, 2009). Pang et al (2014) reported a 42.9 ± 5.5 µm diameter of muscle spindles in the medial gastrocnemius muscles of 9-week-old male and female Sprague-Dawley rats, while Sekiya et al (1986) noted a range of 15-85 µm in Wistar rats 25-35 days after birth.…”
Section: Figure 1 |supporting
confidence: 84%
See 2 more Smart Citations
“…These measurements are consistent with the 42.29 ± 3.04 µm maximal diameter of muscle spindles in the gastrocnemius muscles of adult Lewis rats (Elsohemy et al, 2009). Pang et al (2014) reported a 42.9 ± 5.5 µm diameter of muscle spindles in the medial gastrocnemius muscles of 9-week-old male and female Sprague-Dawley rats, while Sekiya et al (1986) noted a range of 15-85 µm in Wistar rats 25-35 days after birth.…”
Section: Figure 1 |supporting
confidence: 84%
“…Elsohemy et al (2009) found 23.67 ± 2.52 spindles in adult Lewis rats. Pang et al (2014) measured 26.7 ± 2.5 muscle spindles in 9-week-old Sprague-Dawley rats, although they did not distinguish between male and female. These observations additionally suggest that the two heads of the gastrocnemius muscle contain similar numbers of muscle spindles.…”
Section: Figure 1 |mentioning
confidence: 86%
See 1 more Smart Citation
“…5 Schwann cells are essential for peripheral nerve regeneration, and transplanted Schwann cells have been shown to enhance axonal regeneration. 6 Although there have been a few reports 2,[7][8][9] investigating morphological changes and functional recovery of muscle spindles after preservation or repair of afferent innervation, to the best of our knowledge, there have been no reports that examined reinnervation of muscle spindles using cell transplantation procedures. Thus, we transplanted embryonic dorsal root ganglion (DRG) cells, including Schwann cells and sensory neurons, into a Walleriandegenerating nerve and evaluated muscle spindles, the proprioceptive receptors in the skeletal muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the morphological changes of muscle spindles, some authors have reported the influence of peripheral nerve injury, hindlimb unloading and age. 3,8,16,17 After nerve repair, sensory terminals of regenerated muscle spindles are tapered or have irregular forms, but the stretch reflex gradually recovers to normal levels. [18][19][20] Age causes remarkable changes in the structures, not only in the intrafusal muscle but also in sensory nerve endings in muscle spindles.…”
Section: Discussionmentioning
confidence: 99%